Pola Pembinaan Keagamaan Pada Lembaga kesejahteraan Sosial Anak (LKSA) Studi Kasus di LKSA Aisyiyah Kota Batu - Zulfikar Yusuf (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
Religion is a requirement for every individual and community. The Child Welfare Institution, also known as the Lembaga Kesejahteraan Sosial Anak (LKSA) Aisyiyah Batu, is a non-formal institution that strives to foster children and provide social welfare services. It also plays a role in cultivating foster children's faith. Various patterns of religious growth have resulted in foster children with various accomplishments who are trusted by teachers in schools. As a result, scholars seek to look at the religious development pattern of LKSA Aisyiyah Batu. This study employs a qualitative technique in the form of case study research. The foster youngsters who live in the dormitory are the research subjects. Techniques for gathering data include interviews, observation, and documenting. Miles and Huberman's notion is used in the data analysis technique. The study's findings reveal that the religious development pattern in LKSA Aisyiyah intends to promote spiritual potential and foster children to become human beings who believe in God and have noble character. Aqidah, worship, and morals are among the topics covered in class. Coaching employs the lecture, demonstration, habituation, example, warning, and mauidzah approaches. Fardhu prayer, tahajjud, dhuha, sunnah fasting, and tadarus al-Qur'an are common religious practices. The two caregivers who live in the foster children's dormitory bear complete responsibility for fostering, supporting, and evaluating. Two alumni who serve and foster youngsters who have finished their last grades in Senior High School support the two caretakers.